ACO-Optimized DSTATCOM for Reactive Power Compensation in PV-Integrated Weak Grids - Rajasree R; Lakshmi D; Stalin K; Karthick Manoj R; P Jeyarani (Bright Publisher, 2026)
The integration of photovoltaic generation into weak distribution grids introduces voltage instability, reactive power imbalance, harmonic distortion, and prolonged transient response due to low short-circuit capacity and high grid impedance. This study proposes an Ant Colony Optimization-based Distribution Static Synchronous Compensator for improving voltage regulation and power quality in a PV-integrated weak grid. The optimization algorithm is used to tune the proportional–integral controller parameters by minimizing a composite objective involving PCC voltage deviation, reactive power error, total harmonic distortion, feeder power loss, and settling time. The proposed system is modeled in MATLAB/Simulink and evaluated against two benchmark configurations: an uncompensated weak-grid system and a conventional PI-controlled DSTATCOM. The results show that the proposed controller reduces PCC voltage deviation from 0.060 pu to 0.012 pu and reactive power demand from 150 kVAR to 5 kVAR. Total harmonic distortion decreases from 6.5% to 1.6%, while the power factor improves from 0.78 lagging to 0.995. In addition, feeder real-power losses are reduced from 45 kW to 28 kW, and the settling time decreases from 1.8 s to 0.5 s. These findings demonstrate that ACO-based controller tuning provides consistent improvements in voltage regulation, reactive power compensation, harmonic mitigation, feeder efficiency, and dynamic recovery under weak-grid operating conditions.